2015
DOI: 10.4161/15384047.2014.962968
|View full text |Cite
|
Sign up to set email alerts
|

Early treatment with metformin induces resistance against tumor growth in adult rats

Abstract: These authors contributed equally to this work.Keywords: adolescence, antidiabetic, early treatment, metformin, prevention, tumor growth inhibition, Walker 256 tumor Abbreviations: AUC, area under the curve; HOMA-IR, homeostasis model assessment of insulin resistance; HOMA-b, homeostasis model assessment of b-cell function; LBW, body weight loss; MHC-I, major histocompatibility complex class I; NAL, nasal anal length; VEGF, vascular endothelial growth factor.It is known that antidiabetic drug metformin, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Animals that are of different ages when they receive the same stimulus might not respond with the same magnitude because they have differences regarding how they function (Trombini et al . ). The effect of the age of the host on the incidence and growth rate of the Walker 256 carcinosarcoma was investigated by Kerkvliet and Kimeldorf ().…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Animals that are of different ages when they receive the same stimulus might not respond with the same magnitude because they have differences regarding how they function (Trombini et al . ). The effect of the age of the host on the incidence and growth rate of the Walker 256 carcinosarcoma was investigated by Kerkvliet and Kimeldorf ().…”
Section: Discussionmentioning
confidence: 97%
“…) and vascularization during tumourigenesis (Trombini et al . ). Notwithstanding these restrictions, we found similar results in cellular proliferation from Walker 256 tumour‐bearing rats that underwent anaerobic exercise (Lima et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Our laboratory previously demonstrated that metformin could suppress PC proliferation and also inhibit the survival of highly resistant fractions of CSCs/CSLCs screened from PC cells [ 38 ]. Based on preliminary work from our laboratory and others [ 39 , 40 ], metformin has been entered into multiple clinical trials (e.g. NCT01579812).…”
Section: Drug Repurposing Principles Of Network Pharmacology For Gi Cmentioning
confidence: 99%